Distribution and morphometrical variations of stingless bees (Apidae: Meliponini) in urban and forest areas of Penang Island, Malaysia - Suhaila Ab Hamid; Mohammad Sharifuddin Salleh; Kumara Thevan Krishnan; Nur Aida Hashim (Universiti Malaysia Kelantan, 2016)
Stingless bees from four different places in Penang, northern peninsular Malaysia including Universiti Sains Malaysia campus(USM), Botanical Garden, Balik Pulau and Teluk Bahang were sampled randomly and identified. A total of six species of stingless bee were successfully recorded; Heterotrigona itama, Lepidotrigona terminata, Tetrigona apicalis, Tetragonula iridipennis, Tetragonula laeviceps, and Tetragonula pagdeni. Heterotrigona itama is the most abundance species in both urban and forest area. Their hive can be found in all study areas. The results showed that Balik Pulau (forest) had the most diverse stingless bee species (5 species) compared to other selected sites. Morphometrical studies comprising fifteen characters of H.itama were measured. There were significant difference for H. itama body length and appendages between samples collected from urban and forest areas. H.itama in forest areas have larger body size compared to those in the urban area. Overall, stingless bees in urban areas was less diverse compared to forest area.